Planarity correction for 3D objects reconstructed from line drawing - Chen, Xue Chun. (2008)
This projects studies ways of modifying the 3D models so that all the faces are planar. Given that there is an infinite number of a possibility for the planar object, one key issue is to find the optimum-an object with planar faces that deviates from the original objects as little as possible.